Facile synthesis and isolation of 5-hydroxymethylfurfural from diphenyl sulfoxide. Issue 9 (7th April 2021) - Zhang, Tongtong; Hu, Yaoping; Huai, Liyuan; Gao, Zhijin; Zhang, Jian
Abstract : DPhSO was first employed to synthesize HMF from fructose as both the catalyst and solvent, realizing the easy isolation of HMF by water due to the water-immiscible nature of DPhSO. Abstract : We report diphenyl sulfoxide (DPhSO) as an active, cheap and environmentally friendly solvent to facilely synthesize 5-hydroxymethylfurfural (HMF) from fructose. It acts as both the catalyst and solvent to afford nearly 100% conversion of fructose and 68.4% yield of HMF. In particular, HMF was easily extracted using water and DPhSO froze into an insoluble solid at low temperature. DPhSO was reused 6 times without significant loss of activity. The reaction mechanism of DPhSO-catalyzed HMF formation was analyzed by NMR and ESI-MS experiments and theoretical calculations.